Influência da gestão de processos administrativos na segurança de pacientes internados em unidades de terapia intensiva - Santos, Edzângela de Vasconcelos (2014)
In literature, incidents arising from healthcare assistance are well defined. Nevertheless, there are incidents related to administrative processes that are rarely studied, specifically in ICU. This study aims to analyze the influence of the management of administrative processes in the safety of ICU patients. We used descriptive exploratory empirical approach to perform this research. Data from medical records were obtained and collected daily. Additional information form medical and nursing visits were also noted in an appropriate form for reporting safety incidents and, compared with the records in the chart. Double-checking the records with the printed data collection was performed. In this study, 9,396 incidents were found in 202 admissions. Of these, 653 (6.94%) in 148 admissions were classified as administrative incidents. Thus, we conclude that the administrative incidents occupy a small but important portion of total incidents (6.94%), occurring in processes that directly affect the care provided, and may cause serious damage and even death. Almost all safety incidents related to administrative failures were preventable type, therefore fitting the development and implementation of measures to prevent such occurrences, and consequently contributing to the improvement of management and care for critical patients.